CHAIN OF SUSTAINABLE PRODUCTION COSTS AND NATIONAL FOOD SECURITY - Choy Zevallos, Elsa Esther (2015)
Environmental problems exists worldwide; especially in our country, as the result of soil abuse, exploiting it without care for its preservation, and using agrochemicals that damage health, as a result of consuming contaminated fresh food derived from residues of chemical products.A new approach to agricultural chain production is necessary, to ensure sustainable development with economic viability, environmental sustainability, social justice and humanistic, increased capacity for self-knowledge in rural communities- where natural processes are integrated with agricultural production-reaching for higher productivity of plants and organic products. In this regard, the study seeks to answer the following question: What is the impact of implementing a sustainable production system with organic agriculture?The goal is to highlight the importance of implementing organic production processes as sustainable way to improve costs and food security of the population. Also we propose the hypothesis: Organic agriculture is a sustainable production system oriented to efficient management of natural resources and conservation of services provided by ecosystems, generating economic, social and environmental benefits.